Nickel-Catalyzed Favorskii-Type Rearrangement of Cyclobutanone Oxime Esters to Cyclopropanecarbonitriles - Shuai, Bin; Fang, Ping; Mei, Tian-Sheng (Synlett, 2020)
A nickel-catalyzed base-promoted rearrangement of cyclobutanone oxime esters to cyclopropanecarbonitriles was developed. The ring opening of cyclobutanone oxime esters occurs at the sterically less hindered side. A base-promoted nickelacyclobutane intermediate, formed in situ, is assumed to be involved in the formation of the product.
Keywords: nickel catalysis; cyclobutanone oxime esters; cyclopropanecarbonitriles; ring opening; Favorskii rearrangement